Implementasi Pariwisata Berkelanjutan di Pulau Maratua, Kabupaten Berau, Kalimantan Timur - Ilham Junaid (Sekolah Vokasi, Universitas Gadjah Mada, 2019)
The benefits of Maratua Island as tourism attraction should belong to the local community. For this reason, sustainable tourism must be implemented to help community obtain economic benefits and to preserve the natural and cultural resources. This research aims at analysing the implementation of sustainable tourism and proposing recommendations of strategies for sustainable tourism at Maratua Island. This research employs qualitative approach through interviews to the government staff (in tourism board), local community and local leader in Maratua island as well as participant observation in 2017. The research reveals that although the members of community have participated in tourism activity, unsustainable practices by the local community constraint the goal of sustainable tourism. The existence of outsiders (investors) have encouraged the participation of community in tourism. However, the local community should be encouraged to have good job positions rather than as low level worker. This research recommend efforts to achieve sustainable tourism including the importance of socialisation about tourism to community and education and training in creative economy. The government has the role in facilitating such efforts and regulating the investors. Trash boat is considered important in overcoming the issues of environment. In addition, ambassador (duta) of environment and tourism is essential in providing information about tourism and issues on sustainability and sustainable tourism.